Youtube como ambiente virtual de ensino e aprendizagem: características de aulas-live de espanhol - Batista, Fabiana de Freitas (2020)
This research aims to problematize the potentialities of YouTube as a space for teaching and learning Spanish, before and during the COVID-19 pandemic. To this end, we analyzed the main characteristics of live lessons of the YouTube channel “Espanhol para Brasileiros” (“Spanish for Brazilians”) and the didactic strategies used by the teacher, and also discussed some aspects of live transmissions on the platform as a teaching and learning space, taking into account the interactions between teacher and students through written chat. We started from the assumption that the online transmission of the video lesson in a synchronous way allows interaction (LONG, 1996) among the participants, understood as negotiation of meaning “that generates interactional adjustments by the most competent interlocutor”, in this case, the responsible teacher. The research is characterized as exploratory (GIL, 2008), with data collection of 8 live lessons directly from the YouTube channel, analyzed from 4 sets of techniques described by Moore and Kearsley (2005) as strategies related to: a) Humanization, b) Participation, c) Message style and d) Feedback. In the present research we could observe that in the live lessons there is a predominance of humanization, considering, mainly, the fact that they are live broadcasts. There are strong traits of student participation generating the feeling of being virtually together (VALENTE, 2015). As for the message style, we observed the use of more informal language and a great presence of orality marks in the chat, since they are considered virtual chats in real time (MARCUSCHI, 2005). As feedback is concerned, we observed aspects of evaluation in the form of interaction, attested by Paiva (2003), among which there is positive and negative feedback. The results of the analyses showed that, with social isolation imposed by the COVID-19 pandemic, live transmissions through YouTube intensified as a way to minimize the impacts of isolation, which contributed to consider YouTube as a Spanish virtual teaching-learning environment, considering the techniques used to shorten the distance and bring students closer.